Optimizing Hospital Waste Management Systems through Statistical Approaches: Evidence from a Central Java Hospital - Adi Permadi; Viola Lulu Aulia; Aulia Audistia Rohmah; Tiara Eka Supriyanti; Ahmad Lupi (Indonesian Journal of Chemical Engineering, 2025)
Hospital wastewater contains various contaminants that can endanger both environmental and public health if not managed properly. This study investigates the optimization of a hospital wastewater treatment system in Purwokerto using descriptive statistical analysis. Data were collected for the year 2023 from one hospital and included parameters such as Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), ammonia, oils and grease, pH, total coliform, and several heavy metals including cadmium. Results indicate that most parameters met environmental quality standards set by the Ministry of Environment Regulation No. 68/2016, except for total coliform and cadmium, which occasionally exceeded the thresholds. The study suggests several optimization strategies including improved disinfection methods, regular monitoring, technological upgrades, and better staff training to enhance the treatment system's efficiency and ensure compliance with environmental regulations.